P2-S9.03 The sex lives of emergency contraception users in the USA, 2006–2008. (10th July 2011) - Habel, M; Leichliter, J S
Abstract : Background: Previous research indicates that emergency contraception (EC) users are less likely to have visited a gynaecologist in the past 12 months, and are more likely to report ever having an STI compared to non-users; however, studies examining this unique population have been outside of the USA Given FDA-licensure of EC behind-the-counter, this is the first US study to use a nationally representative sample of reproductive aged women (15–44) to explore whether EC users represent a missed opportunity for STI counselling and screening. Methods: Data were collected through in-person interviews and through audio computer-assisted self-interview. Using a sample of 7356 women, sexual behaviour variables for which there were significant bivariate differences (p<0.10) for lifetime EC users were examined in a multiple logistic regression model controlling for demographics often associated with sexual behaviour including age, race/ethnicity, marital status, poverty level, and geographic location. Results: Overall 10% (704) of the sample had ever used EC; less than 3% had used it within the past 12 months. Most women had only used EC once (62%). Primary reasons for use were not using a birth control method (46%) and worry that birth control would not work (42%). Most EC users had received EC from a family planning clinic (51%). More EC users obtained EC from a drug store drug store (23%) than a private doctor's office (17%); most received EC without a prescription (69%). Demographic factors associated with lifetime EC use included: age 20-24/25-29 years (AORs=3.3; 2.4), never married (2.1), income 150% above the poverty level (1.6), and living in an urban-suburban area (1.6). Lifetime EC users were almost twice as likely to have had >4 lifetime partners. In bivariate analyses lifetime EC use was associated with receiving STI services in the past 12 months and having had a pap, but in the model became insignificant. Conclusions: Contrary to previous findings, EC users were no more likely than non-users to have received STI counselling or screening, despite greater numbers of sex partners. However, with licensure of behind-the-counter ECs, this research indicates that some women are accessing ECs without a prescription at drug stores rather than a provider's office, representing a missed opportunity for screening. These findings suggest future research on EC access and possible expansion of STI screening programs into real world settings, such as pharmacies.